THE READABILITY OF ENGLISH TEXTBOOK FOR THE TENTH GRADE STUDENTS OF SMK NEGERI I BINJAI - Floridawaty Siregar and Sortha Silitonga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This research was aimed to find out whether the English reading texts areappropriate or not in terms of the readability level for the tenth grade students ofSMK Negeri 1 Binjai. This study focuses on the readability level of Englishreading texts for grade X students of SMK Negeri 1 Binjai majoring in Bankingclass in the academic year 2015/2016. This study is categorized as descriptivequantitative research. The data of the study was seven reading texts from anEnglish textbook entitled Bahasa Inggris published by Kementerian Pendidikandan Kebudayaan in 2014 with various length and genres as the source of datatested to 30 students as the research sample. The instruments of the research wereFlesch-Kincaid Grade level and Cloze Procedure Test. For the Flesch-KincaidGrade Level Formula, the researcher counts the words, syllables, sentences, theaverage number of words per sentence and the average number of syllables perwords of the reading text to determine the level of readability of the English textsin students’ textbook. The cloze test was used to assess the difficulty in terms of areader’s understanding and response to the structure of the language of a text. Theresults of the study show that based on the cloze test result, the researcher gets theaverage score of 7 reading texts is 57.39% and based on the Flesch-Kincaid GradeLevel Formula the average score is 6 so it can be concluded that reading texts ofBahasa Inggris published by Kementerian Pendidikan dan Kebudayaan in 2014are in the Independent level because the reading texts are readable andunderstandable to the tenth grade students of SMK Negeri 1 Binjai, and the textsare predicted to be quite easy. Therefore, the researcher takes a conclusion thatthis textbook is not appropriate to be used by the students at the tenth gradestudents of SMK Negeri 1 Binjai because they can read them by their own.